The encounter of East Asia with Western civilization in the 19th century: translation as a means of communication - Yu, Jung Hwa (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examines how three East Asian countries - Korea, China, and Japan overcome and translated heterogeneities into a means of communication with Western civilization. Simultaneously, discussions on ways of translation were also examined to compare the stances of each country that accepted Western civilization. The governments of the 3 East Asian countries have commonly encouraged the translation works along with openness to Western civilization in the 19th century. Translation has usually been exploited as a means to rule colonized countries. However, the three countries have spontaneously encouraged translation, suggestive of the need to find alternate approaches to conventional ways in the study of translations in the post-colonial era. In the past, the three countries shared common Chinese characters that facilitated mutual communication. However, their point of view on communication with foreign countries differed. Japan has initiated the translation of the works of Western civilization since 16th century, thus gaining experience in the importance of mutual communication with foreign civilizations. Accordingly, the level of translation and the resultant culture have evolved more than in other countries. China likewise has a long history of translation, but most works of translation were conducted by people of Western origin. In Korea, despite the significant career in the operation of national translational-training school, the public recognition of translation and translators has been relatively negative. This poor acceptance of translation and translators might be the consequence of different results from communication mediated through Korean translation in the 19th century.